2020
DOI: 10.3389/fvets.2020.561371
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Surveillance of Parvoviruses in Commercial Chicken and Turkey Farms in Guangxi, Southern China, During 2014–2019

Abstract: A previously unidentified chicken parvovirus (ChPV) and turkey parvovirus (TuPV) strain, associated with runting-stunting syndrome (RSS) and poultry enteritis and mortality syndrome (PEMS) in turkeys, is now prevalent among chickens in China. In this study, a large-scale surveillance of parvoviruses in chickens and turkeys using conserved PCR assays was performed. We assessed the prevalence of ChPV/TuPV in commercial chicken and turkey farms in China between 2014 and 2019. Parvoviruses were prevalent in 51.73%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…As revealed by the results of Zhang et al (2020), ChPV and TuPV are widely distributed in commercial fowl in some areas of China (e.g., Guangxi). The highest frequency of ChPV positive samples in chickens was 64.18% in broiler chickens, compared with 38.75% in breeder chickens and 38.89% in layer hens [ 14 ]. Moreover, TuPV was detected in 83.33% of the samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As revealed by the results of Zhang et al (2020), ChPV and TuPV are widely distributed in commercial fowl in some areas of China (e.g., Guangxi). The highest frequency of ChPV positive samples in chickens was 64.18% in broiler chickens, compared with 38.75% in breeder chickens and 38.89% in layer hens [ 14 ]. Moreover, TuPV was detected in 83.33% of the samples.…”
Section: Discussionmentioning
confidence: 99%
“…PCR was performed following a previously described method [ 6 , 14 ]. The primers used for pentaplex PCR are listed in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zsak et al [ 4 ] and Nuñez et al [ 26 ] showed that SPF chicks infected with ChPV exhibit obvious clinical symptoms of RSS. In addition, ChPV infections are prevalent in healthy chickens [ 27 ]. Currently, there is no vaccine available to prevent or control ChPV infections, so it is essential to detect the virus to evaluate the impact of ChPV infections.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research by Nuñez et al 23 showed that ChPV was associated with diseases such as enteritis, pancreatitis and pancreatic atrophy. The ChPV and TuPV cases diagnosed in Guangxi, China, from 2014 to 2019 were the first indexed ChPV/TuPV infections in the southern region of China 24 26 and caused enteric disorders and economic losses in the Guangxi poultry industry.…”
Section: Introductionmentioning
confidence: 99%